Fence. Volume two - Pacat, C. S. (BOOM! Box, 2019)
Nicholas is ready for tryouts at King's Row for a spot on the fencing team, but he isn't confident he can win against upperclassmen and his seemingly unbeatable roommate, Seiji Katayama.